N6-methyladenosine participates in mouse hippocampus neurodegeneration via PD-1/PD-L1 pathway - Hu, Wen; Xie, Hongbo; Zeng, Yubing; Pei, Pei; Zhan, Xiaojun; Wang, Shan; Wang, Zhenlin (Frontiers in Neuroscience, 2023)
Developmental abnormalities and hippocampal aging leads to alteration in cognition. In the brain, N6-methyladenosine (m6A) is a common and reversible mRNA alteration that is essential for both neurodevelopment and neurodegeneration. However, its function in the postnatal hippocampus and the specific mechanisms regulating hippocampus-related neurodegeneration still awaits elucidate. We identified dynamic m6A modifications in postnatal hippocampus at different stages (at 10 days postnatally, and at 11 and 64 weeks of age). m6A shows a definite cell-specific methylation profile and m6A modification displays temporal dynamic during neurodevelopment and aging. Differentially methylated transcripts in the aged (64-week-old) hippocampus were enriched in microglia. The PD-1/PD-L1 pathways was identified that may participate in the cognitive dysfunction associated with an aged hippocampus. Furthermore, Mettl3 was spatiotemporally expressed in the postnatal hippocampus, which was highly expressed at the age of 11 weeks compared with the other two timepoints. Ectopic expression of METTL3 in mice hippocampus mediated by lentiviral infection resulted in high expression of genes related to PD-1/PD-L1 pathway and significant spatial cognitive deficit. Together, our data show that m6A dysregulation, which is mediated by METTL3, most likely contributes to cognitive deficits linked to the hippocampus via the PD-1/PD-L1 pathway.